Performance analysis using vertical jump, agility, speed and kicking speed in young soccer players: Influence of age - Garcia-Pinillos, F.; Ruiz-Ariza, A.; Navarro-Martinez, A. V.; Latorre-Roman, P. A. (Apunts Medicina de l'Esport, 2014)
The main objective of this paper was to analyze the influence of age-category in vertical jump ability, sprint, agility and kicking speed in young soccer players.